On the concept of neutrality and its contradictions: The relative neutrality - Pacini, Lorenzo Maria (POLARITIES, 2026)
This paper examines the evolving concept of military neutrality, highlighting its legal, political, and strategic dimensions. Traditionally codified under international law, neutrality requires abstention from armed conflict, impartiality, and non-use of territory for belligerent operations. However, membership in military alliances, such as NATO, fundamentally contradicts these principles due to collective defense obligations and political commitments. The emergence of hybrid warfare, combining conventional, cyber, and unconventional tools, further complicates the application of neutrality, exposing states to ambiguous threats. The study introduces the concept of “relative neutrality,” reflecting partial or domain-specific adherence, offering a framework to analyze neutrality in contemporary, complex conflict environments.